PENGARUH CONTENT MARKETING DAN CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI MARKETPLACE TIKTOK SHOP (STUDI KASUS PADA MASYARAKAT KOTA BIMA) - A. Rahman Azhari; Is Munandar; Ita Purnama (Universitas Mahendradatta, 2025)
This study aims to determine the influence of Content Marketing and CustomerReviews on consumer purchasing decisions on the TikTok Shop Marketplace (Case Study inthe Community of Bima City). The research method used in this study is a survey methodwith a structured questionnaire consisting of 96 respondents as the sample. Data analysisincludes validity testing, reliability testing, classic assumption tests (normality test,multicollinearity test, heteroskedasticity test, and autocorrelation test), multiple regressionanalysis, correlation coefficient, determination coefficient, and hypothesis testing (t-test andF-test) using Statistical Product and Service Solution Ver. 24 (SPSS) software. The researchresults indicate that Content Marketing significantly influences Purchase Decisions,Customer Reviews significantly influence Purchase Decisions, and both Content Marketingand Customer Reviews significantly influence Purchase Decisions.